Freestanding Boron Nitride Nanosheet Films for Ultrafast Oil/Water Separation. Issue 36 (11th August 2016) - Li, Taotao; Wang, Liangjie; Zhang, Kai; Xu, Yancui; Long, Xiaoyang; Gao, Shoujian; Li, Ru; Yao, Yagang
Abstract : Freestanding boron nitride nanosheet (BNNS) films with designed structures are first fabricated by chemical vapor deposition (CVD) methods. As‐prepared freestanding BNNS films exhibit outstanding hydrophobicity and lipophilicity properties. Such brilliant behaviors make them applicable in oil/water separation with very high fluxes up to 1 200 000 L m −2 h −1 bar −1 and excellent separation efficiencies (ppm level in terms of the water content in the filtrate).